2019
DOI: 10.1002/jmri.26713
|View full text |Cite
|
Sign up to set email alerts
|

Cruciate ligament injuries of the knee: A meta‐analysis of the diagnostic performance of 3D MRI

Abstract: Background Despite the advantages of 3D MRI in evaluation of cruciate ligament injuries, its use in clinical practice is still a matter of debate due to controversy regarding its diagnostic performance. Purpose To evaluate the diagnostic performance of 3D MRI for detecting cruciate ligament injuries, using surgery or arthroscopy as the reference standard. Study Type Meta‐analysis. Population Patients with knee pain. Field Strength/Sequence 3D and 2D MRI. Assessment Four databases were reviewed according to PRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…24 Additional oblique scans in the coronal and axial planes improve visualization of the ACL, and a 3-dimensional MRI sequence might provide more information on the ACL rupture characteristics. 1,12,20,22,25,26 Furthermore, it has been reported that MRI performed with the knee in flexion instead of extension improves accuracy in the diagnosis of partial and complete ACL ruptures in general. Although not investigated, this might improve the accuracy of MRI for classifying the characteristics of complete ACL rupture that were investigated in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…24 Additional oblique scans in the coronal and axial planes improve visualization of the ACL, and a 3-dimensional MRI sequence might provide more information on the ACL rupture characteristics. 1,12,20,22,25,26 Furthermore, it has been reported that MRI performed with the knee in flexion instead of extension improves accuracy in the diagnosis of partial and complete ACL ruptures in general. Although not investigated, this might improve the accuracy of MRI for classifying the characteristics of complete ACL rupture that were investigated in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of 22 reports evaluating the diagnostic performance of MRI in detecting cruciate ligament injuries identified 3D MRI to be equivalent to 2D MRI, and 3D MRI at 3 Tesla (T) to be more accurate than at 1.5 T, with surgery or arthroscopy being the reference standard 6 . A study on a fully automated approach for detecting Anterior cruciate ligament (ACL) tears 7 is summarized in the chapter on DL below.…”
Section: Anterior Cruciate Ligament (Acl) Injury and Reconstruction (...mentioning
confidence: 99%
“…The 2D and 3D FSE and TSE pulse sequences have similar diagnostic performance for the detection of articular cartilage defects, meniscus tears, and intercrucial ligament tears in the knee. [22][23][24] 3D Gradient-echo Acquisitions Unlike TSE sequences, GRE sequences use an RF excitation pulse angle α < 90 degrees (►Fig. 2b).…”
Section: D Turbo Spin-echo Acquisitionsmentioning
confidence: 99%